Five-year outcomes of selective laser trabeculoplasty: A retrospective study - Swain, David L.; Eliassi-Rad, Babak (Frontiers in Medicine, 2023)
Studies have shown the efficacy of selective laser trabeculoplasty (SLT) to lower intraocular pressure (IOP) as adjuvant therapy during short-term follow-up. However, few studies have assessed the long-term efficacy of SLT on preventing worsening Humphrey visual field (HVF) parameters and thinning of the retinal nerve fiber layer (RNFL) with continued medical therapy. A retrospective chart review was conducted of 51 eyes of 39 patients with glaucoma treated with SLT at Boston Medical Center between 2012–2016 with 3- and 5-yrs follow-up. Outcome measures included IOP, visual acuity, number of glaucoma medications, number of months to subsequent surgical intervention. HVF outcome measures included mean deviation (MD) and pattern standard deviation (PSD). Optical coherence tomography (OCT) outcome measures included RNFL mean thickness, and superior and inferior thicknesses. Twenty-five eyes received subsequent surgical intervention (mean time to intervention = 33.6 ± 20.0 months). In the eyes that did not receive another intervention, mean IOP was significantly decreased by 3.2 and 3.5 mmHg at 3- and 5-yrs after SLT, respectively. Mean number of glaucoma medications was significantly increased at 5-yrs (2.7 ± 1.6; P = 0.04), compared to pre-SLT (2.0 ± 1.1). Mean HVF MD was significantly higher at 5-yrs (-7.64 ± 6.57 dB) compared to pre-SLT (-5.61 ± 3.90 dB). Mean PSD significantly increased at 3-yrs (5.30 ± 2.91 dB) and 5-yrs (6.84 ± 2.62 dB), compared to pre-SLT (4.63 ± 2.70 dB; P = 0.04 and ≤ 0.01, respectively). On OCT, inferior quadrant RNFL thickness decreased significantly at 5-yrs (88.5 ± 19.3 µm), compared to pre-SLT (94.0 ± 23.2 µm). Although 51% of eyes had IOP controlled at 5-yr post-SLT, mean number of glaucoma medications was significantly higher. Also, there was progression of MD and PSD on HVF and inferior quadrant thinning on OCT at 5-yrs. We found a significant association between age at SLT ≥69 years and risk of subsequent surgical intervention over 5-yr follow-up. Our study adds to our understanding of long-term outcomes of adjuvant SLT for glaucoma patients receiving medical therapy.